Factors Related to Utilization of Traditional Massage on Elderly in Case of Myalgia by Employing Theory of Anderson - Puspita Adie Kurniawati; Rudi Wibowo; Sri Hernawati (Humanistic Network for Science and Technology (HNST), 2019)
Background: The rate number of myalgia in Bondowoso District is on the fourth ranking (7.21%). Myalgia is commonly suffered and found in elderly people. Some patients of myalgia consumed painkiller for a long time. This consumption might deliver risk of side effect like to cause obstacles in erythrocyte (red blood cells) formation, gastritis, or even osteoporosis. The side effect of chemical medicine causes to most of myalgia patient need to have non-pharmacological therapy, particularly traditional massage. The utilization of traditional massage on those elderly patients which aims to resolve complaints of myalgia in District of Bondowoso is lesser than their medical visit to public health center in approximately 1.75% or about 86 clients per month. Methods: This research was conducted with a cross sectional approach and using chi-square test. The sample size this research was 110 informants and taken by purposive random sampling. Results: The results of this research were 69 informants using traditional massage. Further, informants who has as much income per month > 1,801,406 65 people (59.01%). Most informants know as much informnation abaout traditional massage are 68 people (61.08%). Most informants stated that access to traditional massage sites is easily accessible are 93 people (84.05%). Informants who stated that traditional massage facilities meet the requirements of 62 people (56.4%). The informants stated that the quality of traditional massage fulfilled the quality requirements of 65 people (59.01%). Conclusion: Overall, both the factor of probability and need have relation to the utilization of traditional massage. Moreover, the probability factor (service quality and information) has greater determinant relation to this utilization of traditional massage on elderly people in the case of myalgia in District of Bondowoso. Keywords: traditional massage; myalgia; elderly